Pengaruh Model Problem Based-Learning Berbantuan Media Virtual Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik - Andriyani Hastuti; Hairunnisyah Sahidu; Gunawan Gunawan; Ahmad Harjono (Indonesian, 2022)
Conventional teacher-centered instruction has limited the development of students' physics problem-solving skills. This study aimed to analyze the effect of the Problem Based Learning (PBL) model assisted by a virtual laboratory on students' physics problem-solving skills. This study employed a quasi-experimental method using a Nonequivalent Control Group Design. The population consisted of all tenth-grade students of SMKN 1 Lingsar in the 2015/2016 academic year, comprising nine classes. The samples were selected using a purposive sampling technique, resulting in one experimental class and one control class. The research instrument was an essay test measuring physics problem-solving skills. The data were analyzed using homogeneity, normality, and pooled-variance t-tests at a 5% significance level. The results showed that the students in the experimental class achieved higher physics problem-solving skills than those in the control class. The hypothesis testing revealed that the calculated t value (2.58) was greater than the critical t value (2.00), indicating that the Problem Based Learning model assisted by a virtual laboratory had a significant effect on students' physics problem-solving skills. Therefore, the Problem Based Learning model assisted by a virtual laboratory can be considered an effective alternative for improving students' physics problem-solving skills.